DUVERGER, Maurice (2004). Les Constitutions de la France. Editorial PUF, XIV ed. (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2005)
Recensión de la obra: DUVERGER, Maurice (2004). Les Constitutions de la France. Editorial PUF, XIV ed.